ISOLASI DAN IDENTIFIKASI SENYAWA TOKSIK DARI TUMBUHAN Spigelia anthelmia Linn KOLEKSI DARI KAWASAN PANTAI SELATAN, KABUPATEN BANTUL, DAERAH ISTIMEWA YOGYAKARTA - TAUPIK, MUHAMMAD ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Spigelia anthelmia Linn is a plant commonly found in the Pantai Selatan area, the district of Bantul. Its use as a medicinal plant is still not widely known. The purpose of this study is to search the bioactive compound using S. atnhelmia Bioassay model isolation was done using BST (Brine shrimp Lethality test) and the isolated compound to tested further on T47D breast cancer cells and colon cancer cells WiDr. The method extraction using maceration with dichloromethane followed by methanol. Extracts obtained were fractionated using vacuum column chromatography (VCC) silica gel 60 PF254. Active fraction was separated by Preparative Thin Layer Chromatography (TLC Preparative) using silica gel 60 PF254 with mobile phase of chloroform: methanol (9: 1). Isolat A obtained was evaluatd for its LC50 on the brine shrimp test. Isolate A was tasted on T47D cancer and WiDr cells line. Isolat A was identified its structure with IR (Infrared),Liquid Chromatography Mass Spectra (LCMS) C18 column (RP 18) Phenomenex, and Mass Spectrometry (MS) system ESI (Electrospray Ionisation) and NMR spectroscopy (Nuclear Magnetic Resonance). Isolat A had LC50 17.08 ug/ml against Brine shrimp test. Isolat A displayed LC50 value 166.92 ug / ml on T47D cells and 250.24 ug / ml in WiDr cells. Isolat A showed 92.3% purity and has molecular weight at 218 m / z by LCMS. IR data showed the presence of OH, carbonyl and amine groups. Data 1H and 13C NMR spectroscopy showed isolat A has a phenol bonded carbocyclic acids and pyrrolidine frame.